2019
DOI: 10.1039/c9gc01041f
|View full text |Cite|
|
Sign up to set email alerts
|

Boosting the activity of catalytic oxidation of 5-hydroxymethylfurfural to 2,5-diformylfuran over nitrogen-doped manganese oxide catalysts

Abstract: Doping of nitrogen into MnO2 is employed as an efficient catalyst for the catalytic oxidation of HMF to DFF under an oxygen atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 36 publications
2
55
0
Order By: Relevance
“…Additionally, the synthesis of DFF from HMF commonly requires molecular oxygen or expensive transition metal (co)-catalyst (e. g. Ru) which further reduces the applicability of DFF-derived reaction at a higher scale. [26][27][28][29] We conducted the oxidation of HMF in a semi-continuous manner using a column packed with commercial electrolytically precipitated 88 % MnO 2 (Supporting Information, Figure S1) and the toluene alternative 2,2,5,5-tetramethyloxolane (TMO, Figure 1, 14) as the solvent. [30] The non-peroxide forming TMO used in this reaction was recovered and reused after distillation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the synthesis of DFF from HMF commonly requires molecular oxygen or expensive transition metal (co)-catalyst (e. g. Ru) which further reduces the applicability of DFF-derived reaction at a higher scale. [26][27][28][29] We conducted the oxidation of HMF in a semi-continuous manner using a column packed with commercial electrolytically precipitated 88 % MnO 2 (Supporting Information, Figure S1) and the toluene alternative 2,2,5,5-tetramethyloxolane (TMO, Figure 1, 14) as the solvent. [30] The non-peroxide forming TMO used in this reaction was recovered and reused after distillation.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this system did not require the use of inert atmosphere, molecular oxygen or co-catalyst as previously reported. [26,31,32] The solution collected after one passage through the column was analysed by GC-FID to assess the conversion of HMF. If the conversion was not complete, the solution was recirculated through the column.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al [21] have reported iron-based Fe 3 O 4 -SBA-SO 3 H and K-OMS-2 catalysts to obtain a 99 % yield of DFF with 100 % selectivity of 5-HMF in DMSO. Ke et al [22] have reported Nitrogen-doped manganese oxide (N-MnO 2 ) catalysts and showed > 99.9 % selectivity of DFF with a 100 % conversion of 5-HMF. Moreau et al [23] have reported V 2 O 5 /TiO 2 catalysts with 91 % 5-HMF conversion and 93 % selectivity of DFF.…”
Section: Introductionmentioning
confidence: 99%
“…have reported iron‐based Fe 3 O 4 ‐SBA‐SO 3 H and K‐OMS‐2 catalysts to obtain a 99 % yield of DFF with 100 % selectivity of 5‐HMF in DMSO. Ke et al . have reported Nitrogen‐doped manganese oxide (N‐MnO 2 ) catalysts and showed >99.9 % selectivity of DFF with a 100 % conversion of 5‐HMF.…”
Section: Introductionmentioning
confidence: 99%